2001
DOI: 10.1046/j.0016-8025.2001.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependence of shoot hydraulic resistance: implications for stomatal behaviour and hydraulic limitation

Abstract: Recent soil pressurization experiments have shown that stomatal closure in response to high leaf-air humidity gradients can be explained by direct feedback from leaf water potential. The more complex temperature-by-humidity interactive effects on stomatal conductance have not yet been explained fully. Measurements of the change in shoot conductance with temperature were made on Phaseolus vulgaris (common bean) to test whether temperatureinduced changes in the liquid-phase transport capacity could explain these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…1d) did not favor an adequate water recovery because they could generate cavitation in the xylem (Schultz and Matthews, 1997), which is evidenced in the water potential values during the day and the night, despite registering low transpiration rates. The low water potential values before morning that were registered in plants grown in Chia in the fruiting stage, could result from a low temperature during the night that decrease the permeability of the roots and its water conductivity (Matzner and Comstock, 2001;Norisada et al, 2005); these values were close to those reported for grapevines (Vitis vinifera) under water deficit conditions (Tay et al, 2007).…”
Section: Discussionsupporting
confidence: 68%
“…1d) did not favor an adequate water recovery because they could generate cavitation in the xylem (Schultz and Matthews, 1997), which is evidenced in the water potential values during the day and the night, despite registering low transpiration rates. The low water potential values before morning that were registered in plants grown in Chia in the fruiting stage, could result from a low temperature during the night that decrease the permeability of the roots and its water conductivity (Matzner and Comstock, 2001;Norisada et al, 2005); these values were close to those reported for grapevines (Vitis vinifera) under water deficit conditions (Tay et al, 2007).…”
Section: Discussionsupporting
confidence: 68%
“…The greater-than viscosity temperature response of R leaf is consistent with the flow path including a transcellular component (Haines, 1994). This temperature response is the first to be reported for steady-state water flow through individual leaves; previously, milder effects (but still greater than those expected for viscosity) have been reported for leafy shoots (Fredeen and Sage, 1999;Cochard et al, 2000;Matzner and Comstock, 2001). Responses greater than expected from viscosity have also been found for the dehydration of shoots and leaves using the pressure bomb (Tyree et al, 1973(Tyree et al, , 1975Boyer, 1974;Tyree and Cheung, 1977).…”
Section: Partitioning Of Leaf Hydraulic Resistance: Water Flow Througsupporting
confidence: 60%
“…SALIENDRA et al, 1995;FUCHS & LIVINGSTON, 1996;COMSTOCK & MENCUCCINI, 1998). However, interestingly this argument has no support of a recent study by MATZNER & COMSTOCK (2001) who assumed that stomata indeed respond to leaves water status leaves in a drying soil for an herbaceous species (Phaseolus vulgaris L.). Are these evidences for returning to an emphasis away from the soil and towards the shoot of the plant again?…”
Section: Ciência Rural V34 N2 Mar-abr 2004mentioning
confidence: 43%